From expectational conflicts to energy synergies: The evolution of societal value co-creation in energy hub development - T. S. G. H. Rodhouse; E. H. W. J. Cuppen; U. Pesch; Adriaan Ferdinand Correljé (Project Leadership and Society (PLAS), 2023)
Societal value co-creation is an emerging practice in renewable energy projects. Despite its increasing popularity, however, unclarities persist regarding its operationalisation. This paper provides relevant insights by explaining how expectations of societal value co-creation evolved and became performed in a co-creative energy hub project in Emmen, the Netherlands. Over the course of project development, different and sometimes conflicting expectations co-existed of the hub's societal value potential. Drawing on observations, interviews, and document analysis, we describe the developers' efforts to synthesize these different value expectations into a coherent co-creation approach. The results indicate that timing in and of expectations, actor positions and organisational design are influential in how expectations become operationalised in renewable energy projects. Recommendations are provided for the design of societal value co-creation processes in future renewable energy projects.
Keywords: 650; Energy hubs; Expectations; Renewable energy project; Stakeholder engagement; Value co-creation